1979
DOI: 10.1136/bmj.1.6176.1455
|View full text |Cite
|
Sign up to set email alerts
|

Proximal gastric vagotomy, fundoplication, and lesser-curve necrosis.

Abstract: 1455microscopically that the degree of dilatation of the pyloric canal used (4 cm) causes any morphological change in the mucosa or the musculature of the wall. On the other hand, clinical, radiological, and endoscopic evidence shows that the intricate mechanism of the antropyloroduodenal channel is not destroyed, as, for example, in pyloroplasty. Bile reflux was not seen clinically, and no patient developed a postoperative gastric ulcer. We believe that patients return to normal feeding earlier and that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 2 publications
0
19
1
2
Order By: Relevance
“…[13] described 3 patients where increased IGP, due to proximal gastric vagotomy plus fundoplication, probably was a major factor in the develop ment of lesser curvature necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] described 3 patients where increased IGP, due to proximal gastric vagotomy plus fundoplication, probably was a major factor in the develop ment of lesser curvature necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis or ulcer ation at the lesser curvature have occurred in man in the early postoperative period, and localized ischemia is assumed to bean important factor to these complications [5,6,12,14], It has been demonstrated that the intraluminal gastric pressure (IGP) is elevated after proximal gastric vagotomy both in man and experimental animals [2,11,19,21], Elevation of IGP could worsen an ischemia of the stomach wall induced by devascularization [4,8,13], In the present work we, therefore, studied the effect of IGP changes on tissue blood flow in the stomach with regional ischemia caused by devascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Kennedy et al . reported four cases of necrosis of the lesser curvature of the stomach in patients who had undergone this combined procedure and cautioned against its use 37 . Delayed gastric emptying (DGE) was demonstrated in patients who had undergone HSV and fundoplication, compared to those after fundoplication alone by Jamieson et al , although there were no differences between the two groups in terms of symptomatic outcome 38 .…”
Section: Should Hsv Be Added To Antireflux Surgery?mentioning
confidence: 99%
“…Hierzu z~ihlen altersbedingte Sklerose [2,17,18,24], Hypertonie [16,19,24], Diabetes [18] und chronische Niereninsuffizienz [16,18,24]. Aus obigen Oberlegungen erhellt, da6 vornehmlich Krankheitsbilder mit Kompromittierung des Gef~il3systems das Risiko einer MWN steigern (Tabelle 1).…”
Section: Pr?idisponierende Risikofaktorenunclassified